Experimental and Numerical Modal Analysis of Nomex Honeycomb Core Composite Sandwich Spherical Plate - Yiğid, Osman; Şen, Murat (My University, 2025)
This study investigated the dynamic properties of a spherical sandwich composite structure made of carbon fiber face sheets and a Nomex honeycomb core. The structure was produced using the hand lay-up method. The results from Experimental Modal Analysis (EMA) and the numerical model created in ANSYS showed high consistency. The natural frequency difference was only 0.73% for the second mode, with the largest discrepancy of 6.5% was observed in the first mode. These differences are thought to be related to structural variations from the manufacturing process, such as resin distribution, carbon fiber fabric stacking, and air voids and the experimental challenges such as double hit errors, measurement resolutions related to force sensor and accelerometer and environmental noise. The vibration damping capability of the sandwich structure was investigated. Some modes exhibited high damping, while others had relatively lower values. The highest and the lowest damping ratios were obtained as 0.83% for the third mode and 0.23% for the fourth mode. A numerical equivalent model of the structure was created in ANSYS to determine its natural frequencies and vibration modes, confirming its effectiveness in modeling complex structures.
Keywords: Modal analysis; Mode shape; Damping; Spherical sandwich plate; Equivalent model; Experimental modal analysis